Philosophy and the human sciences: Philosophical papers 2 - Taylor, Charles (Cambridge Cambridge University Press, 1985)
Charles Taylor has been one of the most original and influential figures in contemporary philosophy: his 'philosophical anthropology' spans an unusually wide range of theoretical interests and draws creatively on both Anglo-American and Continental traditions in philosophy. A selection of his published papers is presented here in two volumes, structured to indicate the direction and essential unity of the work. He starts from a polemical concern with behaviourism and other reductionist theories (particularly in psychology and the philosophy of language) which aim to model the study of man on the natural sciences. This leads to a general critique of naturalism, its historical development and its importance for modern culture and consciousness; and that in turn points, forward to a positive account of human agency and the self, the constitutive role of language and value, and the scope of practical reason. The volumes jointly present some two decades of work on these fundamental themes, and convey strongly the tenacity, verve and versatility of the author in grappling with them. They will interest a very wide range of philosophers and students of the human sciences.